Validity and Reliability Test of the Office Syndrome Screening Questionnaire - Nusasenjaya, Radite; Raksanagara, Ardini Saptaningsih; Santi, Theresia; Melati, Rima; Purwoko, Reza Yuridian; Ridwansyah, Ridwansyah (Journal La Medihealtico, 2025)
Office Syndrome is increasingly common due to sedentary work environments and inadequate ergonomic practices. This condition is characterized by a variety of symptoms, such as musculoskeletal pain, visual fatigue, sensory disturbances, sleep disturbances, and mental stress, which impact workers’ health and reduce productivity. However, the assessment of this condition is often hampered by the lack of comprehensive and standardized measurement tools. This study aims to develop and test the validity and reliability of an office syndrome screening questionnaire that covers seven dimensions: physical pain, muscle fatigue, visual fatigue, sensory disturbances, decreased productivity, sleep disturbances, and mental stress. The study was conducted cross-sectionally involving 47 office workers in the Jababeka area, Cikarang, who met the inclusion criteria. Data were collected using a questionnaire that was filled out independently via Google Form. Validity testing was carried out using Pearson correlation analysis (items are valid if r > 0.3 and p < 0.05), while reliability testing used Cronbach’s Alpha (reliable if α > 0.7). The results showed that all items had a significant correlation to the total score (p < 0.05), with correlation values ranging from 0.416 to 0.697. The highest correlation was found in the items "Decreased work efficiency" (r = 0.697) and "Difficulty concentrating" (r = 0.673), while the item "Muscle tension" had the lowest correlation (r = 0.416) but was still valid. The overall Cronbach's Alpha was 0.745, indicating good reliability. This screening questionnaire was proven to be valid and reliable to measure symptoms of office syndrome comprehensively.